Advances in Manufacturing Engineering II - Mazurkiewicz, Adam (Diffusion and defect data. Solid state phenomena, 2015)
Collection of selected, peer reviewed papers from the Special topic volume with invited peer reviewed papers only. The 49 papers are grouped as follows:. Chapter 1: Innovative Solutions in Surface Engineering;. Chapter 2: Technologies and Mechatronic Devices for Quality Inspection and Measurements in Industry;. Chapter 3: Advanced Methods for Control Systems and Robotics;. Chapter 4: Researching and Designing of Technologies, Machines and Apparatus for Technological Systems in Mechanical Engineering;. Chapter 5: Industrial Technologies of Waste Recycling and Environmental Engineering.